2000
DOI: 10.1002/(sici)1097-4628(20000509)76:6<938::aid-app21>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of experimental parameters for the quantification of polymer additives using SFE/HPLC

Abstract: Analysis of low concentration additives; for example, antioxidants, in polymeric materials remains a difficult task. In the usual analytical methods, additives are extracted using large quantities of solvents first followed by concentrating the resulting solution for making possible the analysis. The supercritical fluid extraction (SFE) technique eliminates the use of large quantities of solvents and simplifies the analytical procedure. This work has been done with the goal of extracting the antioxidants Irgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Previous studies have shown that NDMA may be present in secondary effluents from sewage treatment systems and in effluents from industries including rubber, leather, pesticides, food processing, foundries and dyes (Chen and Young, 2008;Feng et al, 2009). NDEA, NDBA, NMor and NDPhA have been detected in emulsion products, such as condoms, baby bottle nipples, rubber, soothers and gloves, and in tobacco, meat and wines (Thilen and Shishoo, 2000;Verna et al, 1996). The industrial by-products and domestic discharge containing nitrosamines might be one major source for the investigated source waters.…”
Section: Occurrence Of Multiple Nitrosamines In Source Water and Finimentioning
confidence: 99%
“…Previous studies have shown that NDMA may be present in secondary effluents from sewage treatment systems and in effluents from industries including rubber, leather, pesticides, food processing, foundries and dyes (Chen and Young, 2008;Feng et al, 2009). NDEA, NDBA, NMor and NDPhA have been detected in emulsion products, such as condoms, baby bottle nipples, rubber, soothers and gloves, and in tobacco, meat and wines (Thilen and Shishoo, 2000;Verna et al, 1996). The industrial by-products and domestic discharge containing nitrosamines might be one major source for the investigated source waters.…”
Section: Occurrence Of Multiple Nitrosamines In Source Water and Finimentioning
confidence: 99%
“…The phosphite antioxidant Irgafos 168 is a secondary antioxidant that protects the polymer during processing, 12 so its oxidation product is the main form of this antioxidant in food packagings and it is the analyte determined in this study. On the other hand, the analytical methodology that is used to determine the stability of antioxidants causes per se the oxidation of phosphate 13 ; therefore, it is not possible to quantify the Irgafos 168 levels.…”
Section: Stability Test Proceduresmentioning
confidence: 99%
“…Among the most important and widely used antioxidants are the primary antioxidants Irganox 1010, Irganox 1076 or Irganox 1330, and hydroperoxide decomposers, or secondary antioxidants, namely Irgafos 168, Irgafos P-EPQ, Irgafos 38, and others. [6].…”
Section: Introductionmentioning
confidence: 99%